Effect of dust particle size distribution and intensity variation on microwave signal attenuation prediction - Ahmed, Elfatih AbdelRahman (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Dust storms are meteorological phenomena occur for a percentage of time in arid and semi arid areas especially at African Sahara and Middle East. Measurements at existing microwave links have showed dust storms can potentially result in serious attenuation in signal level especially at Ku band and higher frequencies with direct impact on telecommunications system performance. However, only a limited amount of research has been carried out and the available data was very scarce. Few prediction models have been developed to estimate microwave signal attenuation during the dust storm. Theses prediction models did not incorporate the variation of the dust particle size distribution. Therefore, none of predicted results fitted with the measured results. In this project two dust storm attenuation prediction models have been investigated based on the obtained particle size statistical distributions such as exponential, lognormal, normal and discrete. The estimated attenuation after implementing the effective particle size (re =38.2 μm) at frequency 40 GHz and visibility values 0.625, 1.25, 1.42, 3.75 and 5.56 km were 0.17, 0.09, 0.07, 0.03 and 0.02 dB/km which were close to the measured attenuation 0.14, 0.1,0.07, 0.05 and 0.036 dB/km in Saudi Arabia. Measurements have showed that the dust storm intensity varies horizontally (terrestrial links) and vertically (earth satellite links). All dust storm attenuation prediction models have proposed the attenuation due to dust storm in dB/km and the total attenuation as multiplied by link length assuming that the dust storm is uniformly distributed throughout the microwave link. However, to predict the total attenuation due to dust storm that a microwave link might suffer, an adjustment factor is needed to account for the variation of dust storm intensity along the propagation path. Adjustment factors which reflect the variation of dust storm intensity have been derived based on the analysis of horizontal and vertical dust storm behavior. The estimated total attenuation considering the horizontal dust storm adjustment factor at frequencies 2, 7.5, 10.5, 13 and 40 GHz and visibility levels 0.15, 0.15, 0.05, 0.05 and 0.625 km were 0.6, 0.64, 6.4, 9.8 and 2.2 dB respectively, which were very close to the measured attenuation 0.5, 0.5, 6.4, 10.05 and 2 dB in Sudan and Saudi Arabia.